2008
DOI: 10.1016/j.febslet.2008.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of membrane‐bound cytochrome c oxidase by zinc ions: High‐affinity Zn2+‐binding site at the P‐side of the membrane

Abstract: In the presence of the uncoupler, external zinc ions inhibit rapidly turnover of cytochrome c oxidase reconstituted in phospholipid vesicles or bound to the membrane of intact mitochondria. The effect is promoted by electron leaks into the oxidase during preincubation with Zn 2+ . Inhibition of liposomebound bovine cytochrome oxidase by external Zn 2+ titrates with a K i of 1 ± 0.3 lM. Presumably, the Zn 2+ -binding group at the positively charged side is not reactive in the oxidized enzyme, but becomes access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…Results from earlier studies have shown that the activity of wild-type CytcO is inhibited by zinc ions (Zn 2+ ) (28)(29)(30)(31)(32)(33)(34)(35). One of the suggested Zn 2+ binding sites is located near Asp-132, consistent with structural data of the mitochondrial CytcO (36).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Results from earlier studies have shown that the activity of wild-type CytcO is inhibited by zinc ions (Zn 2+ ) (28)(29)(30)(31)(32)(33)(34)(35). One of the suggested Zn 2+ binding sites is located near Asp-132, consistent with structural data of the mitochondrial CytcO (36).…”
Section: Resultssupporting
confidence: 63%
“…Because proton uptake through the D pathway presumably is not rate limiting for this activity, any effects of Zn 2+ addition may reflect binding to other sites (32)(33)(34). We observed the same decrease in activity upon addition of Zn 2+ to the N139T/D132N as to the wildtype CytcO, which indicates that zinc binding to the other sites was not affected by the D pathway mutations.…”
Section: Resultssupporting
confidence: 51%
“…In fact, incorporation of CcO into liposomes was successfully used for the examination of proton pumping mechanism, ligand binding, etc. [8,9,10]. However, the liposomal turbidity does not permit the use of some of the experimental techniques, such as absorbance spectroscopy or circular dichroism.…”
Section: Introductionmentioning
confidence: 99%
“…Binding of Zn 2+ with the exit proton pathway (from the P‐side of the membrane) in the oxidized CcO required either very long preincubation with μM concentrations of Zn 2+ and the enzyme turning over, or ∼mM concentrations of Zn 2+ [19,20]. Vygodina et al [21] reported that the inhibition of the exit pathway may occur rapidly with Ki of about 1 μM, provided some high potential non‐heme center (e.g. CuB) is reduced prior to onset of the reaction with oxygen.…”
Section: Introductionmentioning
confidence: 99%